Synthetic and computational studies of group 3 and group 4 imido and hydrazido compounds - Mellino, S (2017)
This Thesis describes the synthesis and reactivity of titanium-nitrogen multiply bonded compounds. Mechanistic and bonding studies on titanium imido, hydrazido and borylimido complexes as well as on a novel scandium borylimide recently reported in our research group were described. Chapter 1 provides an introduction to Group 4 and Group 3 metal-nitrogen multiply bonded compounds including synthesis, bonding and reactivity of titanium imido, hydrazido, alkylidene hydrazido and borylimido complexes, (L)Ti=NR, (L)Ti=NNR2, (L)Ti=NNCR2 and (L)Ti=NBR2. Chapter 2 describes the reactions of the hydrazido compound Ti(N2 iPrNMe)(NNPh2)(py) with the Si–H and B–H bonds of silanes and boranes and with H2. The nature and mechanism of these reactions were investigated both computationally and experimentally. Chapter 3 explores a series of new reactions and unprecedented transformations of organic boranes and silanes with titanium half-sandwich compounds. In addition, detailed mechanistic work, using DFT calculations, was performed to understand the chemistry behind these reactions. Chapter 4 describes the bonding and reactivity of novel borylimido compounds. The systematic approach recently implemented in our research group to synthesise new titanium borylimido compounds, is described. A full computational study of the bonding of compounds with sandwich and half-sandwich structures is explained in detail. Chapter 5 explores the experimental attempts to isolate the first scandium borylimido complex performed in our group. DFT and QTAIM and detailed mechanistic study are presented. Chapter 6 contains experimental details, characterising data and DFT energies and coordinates of the optimized structures for the chemistry presented in Chapters Tw-Five.